Multiplicity of Equilibria and Fluctuations in Dynamic Imperfectly Competitive Economies - Chatterjee, Satyajit; Cooper, Russell (American Economic Review, 1989)
This paper investigates two aspects of the macroeconomic consequences of market participation decisions of imperfectly competitive firms. First, can there exist multiple, Pareto-ranked Nash equilibria indexed by the level of market participation? That is, can there exist both thin and thick market equilibria? Second, can the variations in the degree of competition that stem from shocks to preferences and technologies help to understand observed fluctuations in the macroeconomy? This paper is part of an ongoing research program intended to understand the macroeconomic implications of the coordination of economic activities in model economies without complete and/or competitive markets. In such environments, the fundamental theorems of welfare economics do not apply and it is quite possible for the economy to have multiple, Pareto-ranked equilibria. Low-welfare equilibria represent situations in which individual agents, acting noncooperatively, are unable to successfully coordinate their activities and reach a preferred equilibrium-this is termed a coordination failure. In equilibria of this type, there are $100 bills lying on the sidewalk but it takes the effort of more than one individual (i.e., coordination) to reap these gains! Our model relates to two important strands of the literature on coordination failures. First are model economies in which the deviation from the Arrow-Debreu paradigm arises from the market power of sellers (see, for example, Oliver Hart, 1982). In these models, the number of active firms is usually taken to be exogenous. Our contribution is, in part, to allow the number of firms to be determined by the costs and benefits of market participation. This allows us to relate the degree of competition in the economy to variations in fundamentals like technology and preferences in addition to exogenous (but self-fulfilling) variations in expectations. Second, our model represents another example of a participation externality in which the gains to participating in an activity, such as entering a market, depend on the number of other agents participating as well. The papers by Peter Diamond (1982), Chatterjee (1988), and M. Pagano (1987; 1988) explore market participation externalities of a different variety. In Diamond's work, these externalities arise through the matching process, while Chatterjee and Pagano (1987) explore the risk-reducing effects of large markets. Similar externalities are found in the industrial organization literature on networks, as in Michael Katz and Carl Shapiro (1985). The model explored in this paper highlights a participation externality arising from the interaction of imperfectly competitive firms.1 tDiscussants: Robert E. Hall, Stanford University; Peter Diamond, MIT; Olivier J. Blanchard, MIT.